The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-68650-7
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating a Raman spectrometer using an optical pickup unit and pulsed power

Abstract: Young chai cho & Sung il Ahn * Although Raman spectroscopy is a major analytical tool in modern chemical experiments, commercial Raman spectrometers remain very pricey for educational and research purposes in individual university laboratories. thus, this study focused on the structural similarity between the Raman spectrometer and an optical pickup unit (opU), which is an inexpensive compact optical device used for a part of optical discs. the study investigated whether or not a full set of Raman spectrometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Therefore, the intensity of light decreases by 50% every time it passes through the beam splitter, making it difficult to observe a weak Raman signal. Similar issues have been reported in previous studies [ 23 ]. Ag dot reflection mirror was formed by Ag mirror reactions during a lift-off process (Figure S7).…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the intensity of light decreases by 50% every time it passes through the beam splitter, making it difficult to observe a weak Raman signal. Similar issues have been reported in previous studies [ 23 ]. Ag dot reflection mirror was formed by Ag mirror reactions during a lift-off process (Figure S7).…”
Section: Methodssupporting
confidence: 92%
“…In this study, a Raman probe was developed using an OPU because the structural characteristics of a Raman spectrometer are similar to those of an OPU ( Figure 1 a). An OPU-based Raman system has been reported in previous studies [ 23 , 24 ]. However, the fabrication method discussed in previous studies is extremely complicated for educational purposes because of the replacement of multiple OPU parts with optical components.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it ideally suited as a foundation for developing new ultrarapid point-of-use diagnostics. One limitation is that a Raman spectrometer is required, although these can now be fabricated relatively cheaply (∼USD$1000) …”
Section: Resultsmentioning
confidence: 99%
“…One limitation is that a Raman spectrometer is required, although these can now be fabricated relatively cheaply (∼USD$1000). 40 ■ MATERIALS AND METHODS Materials. All aptamers used in this work (Table 6) were acquired from Integrated DNA Technologies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Instead, one can get modular parts from various suppliers (<10,000 USD) to build and configure a Raman spectrometer specifically for electrochemical analysis. Ahn's team demonstrated that using a commercial optical pickup unit, the cost of a functional Raman spectrometer (with performance comparable to commercial ones) can be reduced to below 1,000 USD [63] . An online project named ‘OpenRaman’ (https://www.open-raman.org) even offers an open‐source framework to build individual parts (laser, lens, gating, etc.)…”
Section: Low‐cost In Situ Raman Systemmentioning
confidence: 99%